2015
DOI: 10.1080/15377857.2015.1022629
|View full text |Cite
|
Sign up to set email alerts
|

Political Brand Equity Model: The Integration of Political Brands in Voter Choice

Abstract: The voters' choices about political parties have many similarities in how they make their choices about commercial brands. Therefore, political parties are now constantly applying the concept and strategies of brand management to make the political product attractive, appealable, trustable, differentiable, source of long-term relationship and decision-making driver. Furthermore, the political parties have to play an active role in the community's political socialization processes which are relying heavily on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 121 publications
2
23
0
11
Order By: Relevance
“…If parties accrue advantages from prior experience and continuity, then it stands to reason that parties formed as a breakaway from a bigger party might find it harder to compete. Comparative literature on party branding suggests support for this hypothesis (Ahmed et al 2017;Lupu 2014). Allison (2016) finds that such parties performed poorly in Nicaragua, El Salvador and Guatemala.…”
Section: Organizational Endowmentsmentioning
confidence: 99%
“…If parties accrue advantages from prior experience and continuity, then it stands to reason that parties formed as a breakaway from a bigger party might find it harder to compete. Comparative literature on party branding suggests support for this hypothesis (Ahmed et al 2017;Lupu 2014). Allison (2016) finds that such parties performed poorly in Nicaragua, El Salvador and Guatemala.…”
Section: Organizational Endowmentsmentioning
confidence: 99%
“…Past research suggested the existence of a relevant link between components of brand equity, such as brand image and awareness, and the success of political candidates and parties (Cwalina & Falkowski, 2015;Guzmán & Sierra, 2009; S. W. Nielsen & Larsen, 2014;Smith, 2001). Indeed, human branding is a relevant research topic in politics (Speed, Butler, & Collins, 2015) and voters' choice has been compared to consumers' choice about commercial brands (Ahmed, Lodhi, & Ahmad, 2017). However, the measurement of the positioning and brand image of political actors can be costly and time consuming, when reliant on the use of questionnaires.…”
Section: Brand Importance In Online News and Election Outcomesmentioning
confidence: 99%
“…The findings from stage one of the study will generate insight on how current non-party political brands create, develop and communicate their brand identity from the perspective of elected representatives. For example, the findings will highlight how non-party political brands create-develop communication strategies and tactics, the significance of individual political personality as a tool to provide differentiation and whether personal values are used to characterise the brands (Ahmed et al 2015;Nielsen 2016;O'Cass and Voola 2011;Smith 2008). The findings from stage two of the study will reveal how current non-party political brand image is understood from the perspective of Guernsey voters.…”
Section: Resultsmentioning
confidence: 99%